Microstructure and Geochemical Investigations of Chalcedony - TEKBAS CANDAR, M. (Asian Journal of Chemistry, 2009)
Chalcedony from Turkey has been investigated by scanning-electron microscopy and petrographic microscopy. The geochemical analyses were also carrried out. Chalcedony is a microcrystalline variety of silica SiO2. Wall-lining chalcedony is parallel fibrous consisting of smaller crystallites. Chalcedony is regarded as a secondary, metastable, transitional phase.